The Role of Civic Associations in Ethnic Conflicts in Medan and Ambon, Indonesia - Budi Agustono; Junaidi; Kiki Maulana Affandi; Johan Robert Saimima; Sem Touwe; Julia Lim Pay Loo (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: Various tensions of ethnic conflict had often appeared and disappeared along with the domination of state power throughout the rise and fall of the New Order . From the various regions in Indonesia, ethnic conflicts broke out in the multicultural city of Ambon due to uncontrolled competition for economic and social resources, coupled with other socio-political processes outside of the city. In contrast, ethnic conflicts did not occurred in the city of Medan despite it also had a relatively high competition for resources. The long history of these two regions had a similarity in creating a strong ethnic heterogeneity along with democratisation after the fall of the New Order regime. With the ethnic diversity of these two regions, ethnic conflicts tended to potentially erupt without carrying out any prevention and resolution steps appropriate to the background of the respective regions. This study aims to document the development and activities of the civic associations in Ambon and Medan, as well as to analyse their role in the prevention and resolution of ethnic conflicts in these two regions. This study uses a holistic approach by using various disciplines that are part of the social sciences and humanities clusters. The method used in this study uses a historical and anthropological approach in analysing the comparison of the two regions of study. Civic associations or civil society organisations in Ambon that promote peace and strengthen citizenship played an important role in preventing and resolving conflicts from community initiatives. Meanwhile, the civic associations and civil society organisations in Medan, with their cross-ethnic activities, had driven local democracy, strengthen human rights and promote peace or tolerance, which had positively shaped the plural society in Medan, North Sumatra. Abstrak: Berbagai ketegangan konflik etnis sering muncul dan menghilang seiring dengan dominasi kekuasaan negara sepanjang naik turunnya rezim Orde Baru. Dari berbagai wilayah di Indonesia, konflik etnis meledak di kota multikultural Ambon akibat persaingan ekonomi dan sosial yang tidak terkendali, ditambah dengan proses-proses sosial politik lain di luar kota tersebut. Sebaliknya, konflik etnis tidak terjadi di kota Medan meskipun kota ini juga memiliki tingkat persaingan sumber daya yang relatif tinggi. Dengan keragaman etnis di kedua wilayah tersebut, konflik etnis cenderung berpotensi muncul tanpa adanya langkah pencegahan dan resolusi yang sesuai dengan latar belakang masing-masing daerah. Penelitian ini bertujuan mendokumentasikan perkembangan dan aktivitas asosiasi kewargaan di Ambon dan Medan, serta menganalisis peran mereka dalam pencegahan dan penyelesaian konflik etnis di kedua wilayah tersebut. Studi ini menggunakan pendekatan holistik dengan melibatkan berbagai disiplin dalam rumpun ilmu sosial dan humaniora. Metode yang digunakan adalah pendekatan historis dan antropologis dalam menganalisis perbandingan kedua wilayah penelitian. Asosiasi kewargaan atau organisasi masyarakat sipil di Ambon yang mengedepankan perdamaian dan memperkuat kewargaan berperan penting dalam mencegah serta menyelesaikan konflik melalui inisiatif komunitas. Sementara itu, asosiasi kewargaan dan organisasi masyarakat sipil di Medan, dengan aktivitas lintas etnisnya, mendorong demokrasi lokal, memperkuat hak asasi manusia, serta mempromosikan perdamaian dan toleransi, yang secara positif membentuk masyarakat plural di Medan, Sumatra Utara.